0085 Effect of castration method and analgesia on inflammation and behavior in feedlot cattle. (1st October 2016) - Roberts, S. L.; Hughes, H. D.; Powell, J. G.; Richeson, J. T.
Abstract: There is little agreement on the best castration method in feedlot cattle; a recent USDA survey reported 52.3 and 41.1% of bulls are surgically and band castrated, respectively, and analgesia may mitigate inflammatory pain associated with either method. Our objective was to determine the effect of castration timing (birth vs. feedlot entry), method (surgical vs. banding) and use of the analgesic meloxicam (MEL) on behavior and inflammation in feedlot cattle. This study was a randomized complete block design conducted over a 3-yr period. Single-source Angus × Hereford steer ( n = 42) and bull ( n = 152) calves were randomized at birth to one of five treatments arranged as a 2 × 2 + 1 factorial: (1) steers castrated near birth (CON), (2) bulls surgically castrated without MEL (SUR), (3) bulls surgically castrated with MEL (SUR+MEL), (4) bulls band castrated without MEL (BAN), and (5) bulls band castrated with MEL (BAN+MEL). Upon feedlot arrival (d –10), animals were blocked by initial BW (224 ± 4.5 kg) and assigned randomly to treatment pens ( n = 6). Oral MEL was administered at 1 mg/kg BW concurrent with castration on d 0. Blood samples were collected from a subset of animals ( n = 5 animals/pen) on d 0, 0.25, 1, 4, 7, and 14 to determine haptoglobin (Hp) concentration, as a proxy for inflammation. On d –10, accelerometers were placed on the same subset of cattle to determine baseline and postcastration changes in behavior indicative of pain; activity variables (standing, steps, lying bouts, motion index) were continuously logged and averaged by d. There was a treatment × day interaction ( P = 0.04), with SUR animals having the greatest ( P < 0.01) concentration of Hp on d 1 and 4. Meloxicam administered during surgical castration reduced ( P = 0.01) Hp concentration relative to SUR on d 1. Method of castration had contrasting effects on specific behavior variables. Relative to baseline, standing duration for surgical castration increased 113 min ( P < 0.01), while banding caused 6.7 more lying bouts ( P < 0.01) immediately following castration on d 0. Steps were increased on d 0 for banded (2723), intermediate for CON (2216), and least (1801 steps) for surgical ( P < 0.01). Results suggest that MEL mitigated the more pronounced inflammation observed for surgical castration; whereas, behavior was differentially altered for castration method indicative of a divergent pain response.